Anesthesia and Analgesia Management Profile for Airway Surgeries at Dr. Soetomo General Academic Hospital Surabaya - Salinding, Agustina; Wahyudi, Widiartha; Pradipta, Arya (Faculty of Medicine-Universitas Airlangga, 2022)
Introduction: Ear, Nose, and Throat (ENT) surgeries are commonly performed and very often require the surgeon and anesthesiologist to share the same workspace. Over the years, ENT surgery techniques have evolved from conventional methods to computer-assisted intraoperative navigation. In contrast to the past, a minimally invasive approach to paranasal sinus and petrous bone surgery is now preferred. Bleeding, postoperative nausea, and vomiting are complications often encountered in ENT surgery. In addition, pain management during surgery and patient comfort after a surgical procedure is a challenge for anesthesiologists. Therefore, the choice of anesthetic drugs is important. Objective: This study aims to determine the action profile, anesthetic management, and pain management in ENT surgery at Dr. Soetomo General Academic Hospital Surabaya. Methods: This is a retrospective descriptive study. A total of 177 patients underwent airway surgery. Data were obtained from the Medical Records of the Integrated Surgery Center of Dr. Soetomo General Academic Hospital recorded from January to December 2021. Results: Most of the patients were in the age group of 45 - 65 years (40.1%) and a majority were men (65.5%). Most patients who were â‰¥ 20 years old had a normal nutritional status (54.2%). The most frequent diagnosis was laryngeal cancer (23%), with micro laryngeal surgery being the most frequently performed (35.8%). Most surgeries also needed less than 60 minutes followed by 60 to 119 minutes (27.1%). The most frequently used induction agents were a combination of propofol, fentanyl, and rocuronium (39.5%), with isoflurane as the most frequent inhalation agent (91.3%). Metamizole (70.1%) was the most postoperative analgesic. Conclusion: In general, intravenous agents were used for anesthesia induction. A combination of different induction agents brings synergistic benefits.